Achieving success in nonprofit organizations - Kloppenborg, Timothy J.,; Laning, Laurence J., (2014 digital library., 2014)
This book is aimed at leaders of nonprofit organizations. These leaders include executive directors, managers, board members, pastors, key volunteers, and anyone who wishes to make a difference. The four overarching areas of living the mission, making good decisions, getting things done,and developing your team emerged from literature searches, focus groups, and surveys to discover objectively what critical skills and knowledge are most useful to leaders of nonprofit organizations. Experts contribute individual chapters in each of these four areas. This book can be used as a reference for specific skills and knowledge in any of these areas. It can also be used as a text since it covers 16 specific chapters within the four major sections and each chapter has a major case example, assessment questions, and summaries of key concepts.